Face-to-Face Versus Remote: Effects of an Intervention in Reading Fluency During COVID-19 Pandemic - Cruz, Joana; Mendes, Sofia Abreu; Marques, Sofia; Alves, Diana; Cadime, Irene (Frontiers in Education, 2022)
Fluency is a central skill for successful reading. Research has provided evidence that systematic reading fluency interventions can be effective. However, research is scarce on the effects of interventions delivered remotely versus face-to-face. This study investigated the efficacy of a systematic and standardized intervention for promoting reading fluency in third-grade students (N = 207) during the COVID-19 pandemic. The study had a pretest, posttest, and follow-up design, with two intervention groups (remote vs face-to-face) and a control group. The intervention groups experienced 20 intervention sessions (2 sessions per week), each lasting approximately 50 min. Word reading accuracy, text reading accuracy, and fluency were measured in the three rounds of assessment. In both intervention groups, all measures of reading showed gains from pretest to posttest. The results also suggested that the efficacy of the intervention was similar in the remote and face-to-face modalities. These findings highlight the relevance of systematic interventions in increasing reading fluency and support the use of remote interventions as an adequate alternative to face-to-face interventions.